2008
DOI: 10.2337/db07-0837
|View full text |Cite
|
Sign up to set email alerts
|

Key Role for AMP-Activated Protein Kinase in the Ventromedial Hypothalamus in Regulating Counterregulatory Hormone Responses to Acute Hypoglycemia

Abstract: OBJECTIVE-To examine in vivo in a rodent model the potential role of AMP-activated protein kinase (AMPK) within the ventromedial hypothalamus (VMH) in glucose sensing during hypoglycemia.RESEARCH DESIGN AND METHODS-Using gene silencing technology to selectively downregulate AMPK in the VMH, a key hypothalamic glucose-sensing region, we demonstrate a key role for AMPK in the detection of hypoglycemia. In vivo hyperinsulinemic-hypoglycemic (50 mg dl Ϫ1 ) clamp studies were performed in awake, chronically cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 54 publications
6
111
1
2
Order By: Relevance
“…Consistent with this, down-regulation of a2 in the ventromedial hypothalamus of rats, using short hairpin RNAs delivered by viral vectors, resulted in a defective counter-regulatory response to hypoglycemia, that is, a failure to secrete glucagon from the pancreas and epinephrine from the adrenal medulla (McCrimmon et al 2008). Taken together, these findings suggest that a kinase that evolved to mediate the cell-autonomous response to glucose starvation in singlecelled eukaryotes has retained this function in multicellular organisms.…”
Section: Regulation Of Ampk By Metabolic Stresses Cytokines Drugssupporting
confidence: 65%
“…Consistent with this, down-regulation of a2 in the ventromedial hypothalamus of rats, using short hairpin RNAs delivered by viral vectors, resulted in a defective counter-regulatory response to hypoglycemia, that is, a failure to secrete glucagon from the pancreas and epinephrine from the adrenal medulla (McCrimmon et al 2008). Taken together, these findings suggest that a kinase that evolved to mediate the cell-autonomous response to glucose starvation in singlecelled eukaryotes has retained this function in multicellular organisms.…”
Section: Regulation Of Ampk By Metabolic Stresses Cytokines Drugssupporting
confidence: 65%
“…Pioneering studies in the rat have established the important role that the VMH plays in hypoglycemic counterregulation (28)(29)(30). They have also shown that AMPK plays an important role in this "energy sensing" and that, when activated, it increases the secretion of both epinephrine and glucagon (31,32). Of interest, there was no effect of AMPK activation in the VMH on corticosterone levels in the above studies (31,32).…”
Section: Discussionmentioning
confidence: 95%
“…Mechanisms for generating defective counterregulation may reside further upstream, perhaps at the level of CRH, urocortin, or CRH receptors. Preliminary rodent data from our laboratory suggest that changes in the activation state of CRH receptors in the ventromedial hypothalamus modulate subsequent counterregulatory hormone responses to hypoglycemia (29).…”
Section: Discussionmentioning
confidence: 99%